Health screening for the elderly at Lembah Sari, Rumbai Timur - Eliya Mursyida; Hotmauli Hotmauli; Alfin Surya (Community Empowerment, 2023)
Elderly is the age of someone over 60 years who has decreased physiological function of the body causing non-communicable diseases such as hypertension, arthritis, stroke, chronic obstructive pulmonary disease (COPD), diabetes mellitus (DM), and so on. This service aims to conduct health checks on the elderly in RW 09, Lembah Sari Village, Rumbai Timur as an early detection of non-communicable diseases. The method of implementing community service begins with direct assessment of the elderly accompanied by follow-up of the results of the health screening. The results of the service found that 11 elderly with hypertension, 2 elderly with high diabetes, and 6 elderly with high cholesterol.